2017
DOI: 10.1039/c7ra09291a
|View full text |Cite
|
Sign up to set email alerts
|

Promotion effect of water in catalytic fireplace soot oxidation over silver and platinum

Abstract: The activity of the catalysts in the fireplace soot oxidation depends on water content in the gas feed. Water is partially dissociated with formation of hydroxyls over silver and platinum, which promote soot oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
1
7
1
Order By: Relevance
“…Aneggi et al demonstrated that the zero-oxidation state of silver is favoured on alumina as the support material and concluded that metallic silver is the most active form [22]. However, previous studies [25,41] have shown that AgO x is the active form during the oxidation of soot; in our case, all the catalysts that contained AgO x were the most active. Hence, we concluded that silver oxide was responsible for the good activities of catalysts R2, Ag-AH1 and Ag-AH3.…”
Section: Powder X-ray Diffraction Patterns Of the Catalystscontrasting
confidence: 46%
See 2 more Smart Citations
“…Aneggi et al demonstrated that the zero-oxidation state of silver is favoured on alumina as the support material and concluded that metallic silver is the most active form [22]. However, previous studies [25,41] have shown that AgO x is the active form during the oxidation of soot; in our case, all the catalysts that contained AgO x were the most active. Hence, we concluded that silver oxide was responsible for the good activities of catalysts R2, Ag-AH1 and Ag-AH3.…”
Section: Powder X-ray Diffraction Patterns Of the Catalystscontrasting
confidence: 46%
“…In diesel particulate filters, NO2 oxidises soot, whereas in our study NO or NO2 were not present during the measurements. It is likely that the oxidation of soot with the Pt catalyst required the assistance of NO; hence, Pt alone was unable to efficiently oxidise soot because the level of NO2 generated under fireplace conditions was rather low [25,26]. Figure 5 shows the soot-oxidation temperature as a function of the dispersiveness of the active metals in the catalyst in this study.…”
Section: Steady-state Soot-oxidation Activitymentioning
confidence: 94%
See 1 more Smart Citation
“…The use of catalytic converters has been explored at the laboratory and pilot scale, focusing on the major primary pollutants including gases and primary particles, but studies lack any assessment of SOA abatement. As the application of catalytic converters remains challenging, , further scientific studies are needed to establish their potential, especially when trace pollutants are considered.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the soot oxidation of the SCC tubes, the tubes could be coated with a soot oxidation catalyst. For example, aluminum oxide-supported silver catalysts have displayed reasonably low temperature soot oxidation performance, and could be utilized to clean the tubes at a temperature as low as 310 • C [33,42]. respectively.…”
Section: Long-term Scc Performance Under Sooty Conditionsmentioning
confidence: 99%